INCIDENCE OF LUNG CANCER AND GASTRIC CANCER IN KEMEROVO REGION FROM 1996 TO 2015 - LARIN, S.A.; MUN, S.A.; BRAILOVSKIY, V.V.; MAGARILL, Yu.A.; POPOV, A.N.; EREMINA, N.A. (Fundamental and Clinical Medicine, 2017)
Aim. To study the incidence of lung cancer (LC) and gastric cancer (GC) in Kemerovo Region from 1996 to 2015. Materials and Methods. We collected standardized epidemiological data on incidence of LC and GC following comparison of the trends between 1996-2005 and 2006-2015. Results. Incidence of lung cancer and gastric cancer in Kemerovo Region reduced from 49.0 to 36.7 and from 36.4 to 20.5 cases per 100,000 population, respectively, from 1996 to 2015. The proportion of inhabitants living within the territories with the high level of LC and GC incidence decreased from 58.8% to 7.2% and from 52.4 to 7.6%, respectively, in 2006-2015 compared to 1996-2005. Local administrative units of Kemerovo Region had the local features in incidence of LC and GC. Conclusions. Decrease in incidence of LC and GC is evident and is possibly caused by the decrease in exposure to chemical carcinogens.